Government Governance Moderate Foreign Direct Investment and Debt Stock on Tax Revenue - Febriana, Hanin; Wijaya, Suparna; Arieftiara, Dianwicaksih (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the effect of foreign direct investment (FDI) and debt stock on tax revenue, which is moderated by government governance variables. Methodology/approach: This research is quantitative research that uses a purposive sampling method to take samples. The samples taken were all from the population in South Asia, namely India, Sri Lanka, Nepal, Afghanistan, Maldives, Bangladesh, Bhutan, and Pakistan, resulting in 76 observations. The data analyzed were in the form of panel data in the form of secondary data obtained from the World Bank database. Panel data have the advantage of allowing a cross-sectional analysis of data on the same units over several time periods. Results: The research results show that variable foreign direct investment has a significant positive influence on tax revenue, while the debt stock variable has a significant negative influence. After adding the government governance moderation variable, the results are found that the foreign direct investment and debt stock variables have a significant positive influence Limitations: The limitation of this research is that it uses a small population of research objects, so that it can be added to the number of countries used as research objects. Contributions: This research will have a good contribution to the development of knowledge in the fields of financial accounting and taxation.